2003
DOI: 10.1097/00000542-200307000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Chronic Intrathecal Morphine Infusion in a Sheep Model

Abstract: The toxicity of intrathecal morphine seems to be dependent on the amount of morphine infused, although the effects of dose versus concentration cannot be clearly distinguished in this study. Intrathecal morphine doses of 12- 18 mg/day produced inflammatory masses extending from the catheter tip down the length of the catheter within the subarachnoid space. Doses of 6-9 mg/day produced mild-to-moderate inflammation 5 cm cranial to the catheter tip. A dose of 3 mg/day produced no neurotoxicity and spinal histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 34 publications
2
71
0
Order By: Relevance
“…These models include continuous infusion in larger animals in order to assess, for example, development of mass-occupying granulomas which are a concentration-dependent (Gradert et al, 2003) and ligand-dependent (Yaksh et al, 2013) outcome of some intrathecally infused agents. The large animal models closely parallel the human experience in terms of this adverse effect and, therefore, represent a well-validated model for assessment of toxicity of agents intended for spinal infusion.…”
Section: Intrathecal Drug Deliverymentioning
confidence: 99%
“…These models include continuous infusion in larger animals in order to assess, for example, development of mass-occupying granulomas which are a concentration-dependent (Gradert et al, 2003) and ligand-dependent (Yaksh et al, 2013) outcome of some intrathecally infused agents. The large animal models closely parallel the human experience in terms of this adverse effect and, therefore, represent a well-validated model for assessment of toxicity of agents intended for spinal infusion.…”
Section: Intrathecal Drug Deliverymentioning
confidence: 99%
“…31 Preclinical studies have emphasized that at a dose of 12-18 mg/ml/day or higher, there is a 100 % incidence of granulomas in the dog 12 and sheep. 32 Systematic studies suggested that the risk of granuloma formation is correlated with local CSF concentrations. 33 Interestingly, sampling lumbar CSF in dogs proximal to the catheter tip have shown in acute pharmacokinetic studies that at the 12 mg/ml/day dose, CSF concentrations were on the order of 42,000 ng/mL.…”
Section: Changes In Drug Delivery and Csf/plasma Concentrationsmentioning
confidence: 99%
“…A small number of experimental scenarios tested in 2 animal subjects in a preliminary pilot study cannot prove definitively that CSF pressure-based methods will successfully diagnose the broad range of intrathecal catheter malfunctions that occur in actual patients. For example, studies of other clinically important drugand catheter-related issues, such as inflammatory mass, could be performed in established canine or ovine laboratory models [9,10] . The principal goal of the early experiments described here -to confirm or falsify the notion that commonplace bedside observations of CSF pressure waves can be adapted to diagnose and/or troubleshoot intrathecal catheters noninvasively -appears to have been achieved with encouraging, albeit preliminary, results.…”
Section: Limitationsmentioning
confidence: 99%